(untitled) (American Journal of Business Management, Economics and Banking, 2023)
In the present article is given investment environment in attracting of investments and capital flow. In particular is offered investment environment of developed countries of the World and criteria of assessment of investment environment in investments involving process. Studied the investment environment of the USA, Germany and other developed countries.